Faktor-Faktor yang Mempengaruhi Kinerja Lembaga Keuangan Mikro Syari’ah dengan Menggunakan Metode Indonesia Zakat Development Report (IZDR) - Zamzami, R. Mohd.; Zuhri, Saifudin (IAIN Salatiga, 2015)
This research aims to measure the performance of BMT Hudatama and UJKSAl-Hidayat as two Islamic Microfinance Institutions in Semarang, Central Java. Research method used in this study is performance measurement tools issued by Indonesia Magnificence of Zakat (IMZ) in Indonesia Zakat and Development Report (IZDR) in 2011. This method includes five measurement indicators; 1) Islamic compliance, legality, and institutional performances;2) Management performance; 3) Financial performance; 4) Economic efficiency; and 5) Social legitimacy performance. This study used primary and secondary data. Primary data were taken from interview and BMT Hudatama and Islamic Financial Service Unit of Al-Hidayaat’s annual report. Secondary data were obtained from review of related literature. The comparison between the two institutions indicates that BMT Hudatama is better than UJKS AL-Hidayat in terms of its performance. However, the comparison with U test or Mann whitney U Test indicates that there is no significant difference between the performace of the two institutionsPenelitian ini bertujuan untuk mengukur kinerja Lembaga Keuangan Mikro Syari’ah (LKMS) yaitu BMT Hudatama dan UJKS Al-Hidayaat di Kab/KotaSemarang Jawa Tengah. Metode yang digunakan adalah metode pengukurankinerja prima yang dikeluarkan oleh Indonesia Magnificence of Zakat (IMZ)dalam Indonesia Zakat and Development Report (IZDR) 2011 mencakuplima indikator pengukuran yaitu: 1) Kinerja kepatuhan syari’ah, legalitasdan kelembagaan, 2) Kinerja Manajemen, 3) Kinerja Keuangan, 4) KinerjaPendayagunaan Ekonomi, dan 5) Kinerja Legitimasi Sosial. Penelitian inimenggunakan data primer dan data sekunder. Data primer diperoleh dariwawancara dan laporan tahunan dari BMT Hudatama dan Unit Jasa KeuanganSyari’ah Al Hidayaat. Sedangkan data sekunder diperoleh dengan melakukanstudi literatur yang berkaitan dengan penelitian.Dalam perbandingan kinerjaprima BMT Hudatama lebih baik dari UJKS Al-Hidayaat. Namun dalamperbandingan dengan menggunakan uji U atau Mann whitney U Test untukmelihat signifikansi perbedaannya, didapatkan tidak ada perbedaan yangsignfikan kinerja prima BMT Hudatama dan UJKS Al-Hidayaat